Wayang Sasak as a Media for Dakwah Case Study of Ki Dalang Buwana Sanggar H. Safwan, AR in Batu Rimpang Dusun Badrain Village Narmada District, West Lombok Regency - Sauri, Sopiyan; Kurnia, Wahyu; Permana, Beny; Junaidi, Junaidi; Subhan, Subhan (Gema Cendekia Institute, 2024)
Shadow puppets, a cultural gem of Indonesia, embody acting, sound, music, literature, sculpture, and symbolism. For the Sasak people, puppets hold deep significance as a medium of communication and entertainment, enabling the delivery of Islamic dakwah messages through their storylines. This study focuses on how puppeteer Ki Dalang H. Safwan, AR, of Sanggar Buwana in Batu Rimpang, West Lombok, conveys dakwah messages during puppet performances. Using a descriptive qualitative approach, data were collected via observation, interviews, and documentation. The findings highlight the puppeteer's efforts to integrate dakwah messages, which resonate with audiences by incorporating philosophy and noble values. Puppet performances significantly influence fans, offering life lessons in engaging ways. However, challenges persist: limited publicity restricts audiences to local villagers, funding constraints prevent adding personnel to attract more viewers, and younger generations show declining interest in puppetry. Despite these obstacles, shadow puppetry remains a culturally valuable and impactful tool for communication and education within Sasak society, bridging tradition and Islamic values for the community's benefit. The art form continues to be a reflection of cultural heritage and moral guidance.